Biodiversity Beyond National Jurisdiction: Regimes and Their Interaction - Margaret A. Young; Andrew Friedman (AJIL Unbound, 2018)
International efforts to better conserve the marine biological diversity of areas beyond national jurisdiction (BBNJ) through a new international legally binding instrument1 are developing in a context of established norms and institutions. Existing regimes already address specific marine sectors (such as shipping), regions (such as fishing in the South East Atlantic), species (such as whales), and even underlying customary international law and territorial concepts (including the boundaries of the “high seas”2). States have agreed that they will not “undermine” these existing frameworks.3 We seek to contextualize this commitment within the fragmentation of international law and the interaction between regimes.4 We argue that international law-making should not be overly restricted by deference to existing competencies and mandates, which are fluid and asymmetrically supported. An inclusive and adaptive approach to existing and future institutions is vital in the ongoing quest for integrated and effective oceans governance.